Dilema Mobilitas Kerja dan Tinggal di Rumah terhadap Laju Penyebaran Kasus Covid-19 di Indonesia - Intan Azqia (PPJP Universitas Lambung Mangkurat, 2023)
This research was conducted to determine the speed of the spread of Covid-19, which is the most significant dilemma felt by the population, especially in work mobility and staying at home. In a situation like this, it is very influential on the progress of the population's economy.This type of research is in the form of quantitative research, and the data used in this research are data from Quarter I 2020 Quarter I 2021 obtained from the National Statistics Agency, national and provincial Covid-19 data from Kawalcovid-19 and Population Mobility Data from the Community Mobility report. during the Covid-19 pandemic. The analytical method used is panel data regression analysis with classical assumption testing.The results of this study in regression model 1 show that the Variables of Economic Growth, Population, Work Mobility, and Home Mobility have a positive and significant impact on the rate of spread of Covid-19 cases. The results of this study in regression model 2 show that the Variables of Economic Growth, GRDP Per Capita, Population, Home Mobility, Hotel Mobility have a negative and insignificant effect on the rate of spread of Covid-19 incidence